2022 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW) 2022
DOI: 10.1109/vrw55335.2022.00098
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of an immersive ultrasound-guided locoregional anesthesia simulator

Abstract: Figure 1: The user interface of the immersive ultrasound-guided locoregional anesthesia simulator. (Bottom left) The Virtual scene with the virtual instruments manipulated by the user and the ultrasound screen displays the ultrasound image.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(50 reference statements)
0
0
0
Order By: Relevance
“…Similarly to Simon et al [44], our evaluation revealed that the haptic feedback is the main limitation of face validation. Although the haptic feedback does not realistically simulate touch sensations from a real liver, nearly all participants stated that the haptic feedback is supportive.…”
Section: Ultrasound Simulationsupporting
confidence: 80%
See 1 more Smart Citation
“…Similarly to Simon et al [44], our evaluation revealed that the haptic feedback is the main limitation of face validation. Although the haptic feedback does not realistically simulate touch sensations from a real liver, nearly all participants stated that the haptic feedback is supportive.…”
Section: Ultrasound Simulationsupporting
confidence: 80%
“…However, only a few approaches focus on US training directly addressing visuospatial skills. Simon et al [44] identified the lack of training focusing on hand-eye coordination in the case of US-guided needle intervention for anesthesia. To manipulate the US probe and needle, they used two Geomagic Touch devices.…”
Section: Virtual Ultrasound Trainingmentioning
confidence: 99%